PEMBELAJARAN MATEMATIKA STATISTIK BERBANTUAN WEBSITE GOOGLE SITES (QUIZIZZ) DI KELAS V SDN 1 TAMANWINANGUN - Nurhayati, Nurhayati; Irfan, Muhammad; Istiqomah, Istiqomah; Ulfa Diana, Anissa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In statistical material in grade 5 mathematics, students still experience difficulties, especially in terms of presenting data. Therefore, a learning method is needed that can help students overcome their difficulties in presenting statistical data. One alternative that can be done by the teacher is the presentation of learning media using the Google Sites Website (Quizizz). This study used descriptive qualitative method. The research data were obtained from school principals, teachers and students. Data collection techniques in this study were obtained through observation and interviews. Data analysis was carried out by (1) data reduction; researchers carry out the process of selecting or selecting, focusing or centralizing, simplifying, and abstracting from all types of information that support research data. (2) Data presentation; A collection of information that enables the researcher to draw conclusions and take action. (3) Drawing conclusions; The researcher must strive to understand the data under scrutiny, thoroughly and in depth. The evaluation technique used to check the validity of the data is triangulation. The triangulation used is source triangulation and method triangulation. The results of this study indicate that (1) The use of the google sites website (quizizz) can make students active in learning Mathematics Statistics in data presentation material in grade 5. (2) Google site-assisted website media can help students repeat lessons without being bound by time and place. (3) Embedding Quizizz in evaluation exercises on Google Sites can improve students' ability to present statistical data.